(3MeGjI GdeSJgdc aj Gdabg GdGbJUGOj GdGSdGej(B-(3OQGSI ebGQfI(B- /s - (3YHOg, ehab eMeOs ((3YeGf(B: s (3GdeLOdGhj(B, s, 2002)
(3GdGSJgdGc,GdGfJGL,GdhSGFd GdJj GJHYgG GdGSdGe dMeGjI GdeSJgdcs
(3GdeQGLY U(B.339s
Keywords: (3GdeSJgdchfs; (3MeGjI GdeSJgdcs